The value to banks of small business lending - Dmytro Holod; Joe Peek (Federal Reserve Bank of Boston, 2013)
By estimating the market premium placed on the small business loan portfolios of banking organizations, this study provides direct evidence on the value to banks arising from relationship lending. Using data from the small business loan survey contained in the June bank call reports, we find that small commercial and industrial loans do, in fact, add value for smaller banking organizations, both in absolute terms and relative to the value contributed by larger commercial and industrial loans. Interestingly, the value-enhancing effect emanates primarily from the smallest loans, those with original values of 100,000 or less. On the other hand, small commercial real estate loans, being transactional rather than relationship in nature, do not contribute additional value to banking organizations relative to larger commercial real estate loans.
Keywords: G21; 330